The effects of simulated and actual visual impairment on the Montreal Cognitive Assessment - Stark, Zoey; Morrice, Elliot; Murphy, Caitlin; Wittich, Walter; Johnson, Aaron P. (Aging, Neuropsychology, and Cognition, 2023)
Many cognitive assessments include a visual component; however, adults may experience a decline in visual acuity with age. Scores on cognitive assessments of adults with visual impairments are typically lower than adults with normal vision, however, it is unclear if these lower scores are a consequence of cognitive or visual impairment. We measured the impact of simulated visual impairment on a cognitive screening measure. Undergraduate students were administered the Montreal Cognitive Assessment (MoCA) under three vision conditions (20/20, simulated 20/80, simulated 20/200). We found a main effect of vision condition on test performance such that there is a statistically significant difference between scores on the 20/20 and 20/80 conditions and 20/200. However, no differences were observed between 20/80 and 20/200. Participants' performance decreased with simulated impairments. A secondary between-subject analysis was conducted on a sample of older adults with and without vision impairment; no differences were found.